Analisis Yuridis Peran Amicus Curae Dalam Sengketa Hasil Pilpres Di Mahkamah Konstitusi (Studi Kasus : Perkara PHPU.PRES/XXII/2024) - Meita Lefi; Dola Riza; Rani Fepriana (Fakultas Hukum Universitas Tamansiswa Padang, 2026)
The dispute over the 2024 Presidential Election (Pilpres) results at the Constitutional Court (MK) has become a public spotlight, particularly with the emergence of the amicus curiae phenomenon, or